Studi Kasus Pengolahan Air PLTU Y 1×660 MW dengan LCA - Ilham Satria Raditya Putra; Arie Dipareza Syafe'i (Dampak, 2025)
Water treatment plays a vital role in supporting coal fired power plant operations. This process influences the quality of demineralization water used as boiler feed water and cooling media. Furthermore, the post-treatment process before discharge into water bodies also determines the extent of environmental impact. This study presents a Life Cycle Assessment (LCA) of a coal-fired power plant’s water treatment. The study aims to evaluate the environmental impacts of the water treatment process, including chemical usage and waste management as a by-product from the treatment of water quality, and also determine the process point with the significant impact. These steps include defining the purpose and scope, inventorying and assessing life cycle impacts, and interpretation. Through an approach using the CML IA Baseline and ReCiPe 2016 Midpoint, the impact assessment focused on the effects that influence the sustainability of terrestrial and aquatic ecosystems such as marine aquatic ecotoxicity, human toxicity, and other impacts. The impact assessment indicates that the significant environmental impact is influenced by chemicals, especially the coagulant and hazardous waste such as used oil and used hazardous packaging. This influences the high environmental impacts such as marine aquatic ecotoxicity, terrestrial ecotoxicity, human carcinogenic toxicity, and global warming potential. The implementation strategy of environmental programs is carried out, such as the substitution of FeCl3 to Al2(SO4)3, reuse of used hazardous packaging, and processing used oil into vehicle oil. This study can provide an overview for similar industries in optimizing power plant water treatment processes towards sustainable operations.   Keyword: environmental program, life cycle assessment, risk management, water treatment